Oxford international primary English Student book 3 - Barber, Alison; Hearn, Izabella; Murby, Myra (Pakistan: Oxford international primary, 2022)
The Oxford International Primary English Student Book 3 for the Pakistan edition is crafted to build foundational English language skills in young learners. It features a range of engaging texts, including stories, poems, and informational passages, designed to develop reading comprehension, writing, speaking, and listening abilities. The book includes interactive activities and exercises that promote vocabulary growth, grammar understanding, and creative expression. Tailored to fit international educational standards while reflecting the local context, it aims to make learning English both effective and enjoyable for students in Pakistan.
Keywords: English - Text Book